Contrastive Linguistics, Language-Pair Translation Studies, and Language Variation in the Context of German Linguistics in Italian Universities - Costa, Marcella (ANNALI. SEZIONE GERMANICA. Rivista del Dipartimento di Studi Letterari, Linguistici e Comparati dell’Università degli studi di Napoli L’Orientale, 2021)
This methodologically oriented paper illustrates the relevance of translation-oriented contrastive linguistics for university translation didactics, i.e. an applicative contrastive linguistics that combines the usually system-oriented, static language comparison with the dynamic approach of language pair-related translation studies. I illustrate this method and its application in translators training courses by means of a language pair-related translation problem, namely the rendering of alterati, especially augmentative and pejorative forms, from Italian into German and vice versa.